Brickwork wall models strengthened with diagonal and horizontal GFRP strips. (1st September 2021) - Capozucca, R.; Magagnini, E.
Abstract: The use of fiber reinforced polymers (FRPs) as external bonded (EB) strengthening of unreinforced brickwork masonry has became a common intervention technique for restoration of masonry walls damaged by seismic actions with the aim to improve the capacity under in-plane shear loading. The exact knowledge of the behavior of system composed by masonry and EB FRP strips through the interaction mechanism between strengthening and substrate is essential for the effectiveness of interventions based on the use of FRP strips. This paper provides an investigation on the behaviour of unreinforced and reinforced masonry walls made with solid clay bricks in scale 1/3rd, considering the presence of different types of masonry, such as historic and modern, and different configuration of the GFRP strengthening. Three walls, characterized by double T shape, were tested under combined compression and shear loading. Two of them were strengthened after damage using, respectively, diagonal and horizontal EB GFRP strips; another one was strengthened with horizontal GFRP strips without damage and subjected to the same loading path until failure. The response of all models is illustrated and discussed considering the walls' shear strength and effects on the failure mechanism due to diagonal and horizontal EB GFRP strips.